TEACHING LISTENING COMPREHENSION BY USING INTERACTIVE LISTENING CLASSROOM PERFORMANCE - Herlina Herlina; Marleni Marleni (Universitas PGRI Palembang, 2019)
The problem of the research discussed in this study â€œIs it effective to teach listening comprehension by using interactive listening classroom to the first semester students of I.b class of English Education Study Program-PGRI University Palembang?â€ Based on the problem, the writerâ€™s objective of the study was to find out whether or not it is effective to teach listening by using interactive listening classroom performance to the first semester students of I.b class of English Education Study Program-PGRI University Palembang. In this study, the method was used the pre experimental design with the one group pre-test and post-test. The population of this study was the first semester students of English Education Study Program-PGRI University Palembang. The sample of this study was Ib consisted of 34 students the sample was taken by using purposive non random sampling the data were collected and analyzed by means of two statistical analyses, Matched t-test and percentage analysis. The finding of this study showed that the average score in pre-test was 51.91 and the average score in post-test was 84.11, the result of matched t- test was 14.70, which exceeded the critical value ( 1.697 ). It means that null hypotheses (Ho) was rejected and alternative hypotheses (Ha) was accepted. So teaching listening comprehension by using interactive listening classroom performance was effective.